Effect of Nursing Managerial Competencies on Organizational Performance: The Mediating Role of Nursing Environments - Jiae Lee (JONA: The Journal of Nursing Administration, 2026)
Objective: This study examined the mediating role of nursing work environments in the link between managerial competencies and organizational performance among nurse unit managers. Background: Nurse unit managers bridge hospital goals and frontline care, yet how their competencies influence organizational performance through work environments remains unclear. Methods: A cross-sectional survey of 200 nurse unit managers was conducted, and mediation analysis was performed using PROCESS Macro. Results: Both nursing managerial competencies (B=0.19, P =0.014) and work environments (B=0.84, P